Effect of Clostridium butyricum and Butyrate on Intestinal Barrier Functions: Study of a Rat Model of Severe Acute Pancreatitis With Intra-Abdominal Hypertension - Zhao, Han-bing; Jia, Lin; Yan, Qing-qing; Deng, Qi; Wei, Bo (Frontiers in Physiology, 2020)
Background/Aims: Severe acute pancreatitis (SAP) is associated with intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS), but treatment of these conditions is difficult. We studied a rat model of SAP+IAH to determine the effect of oral administration of Clostridium butyricum and butyrate (its major metabolite) on intestinal barrier functions. Methods: A total of 48 rats were assigned to 4 groups, with 12 rats per group: Sham, SAP+IAH, an SAP+IAH+C. butyricum, and SAP+IAH+butyrate. SAP was induced by sodium taurocholate infusion into the biliopancreatic duct, intra-abdominal pressure (IAP) was measured 24 h later, and rats were then euthanized. The plasma levels of four markers were determined (amylase, diamine oxidase [DAO], and lipopolysaccharide [LPS]). The pancreas and intestine were examined using histology, and RT-PCR and western blotting of intestinal tissues were used to measure the expression of five markers (tight junction proteins [ZO-1, claudin-1, occludin], MMP9, and TNF-α). The gut flora of the rats were examined by 16S rRNA sequencing. Results: Induction of SAP+IAH altered several functions of the intestinal barrier, and decreased the levels of TJ proteins, the richness and diversity of the microflora community, the relative abundance of Firmicutes, and the number of probiotic organisms. However, induction of SAP+IAH increased the expression of MMP9 and TNF-α, and the relative abundance of Proteobacteria and pathogens in the feces. Rats that received oral C. butyricum or butyrate had reduced intestinal injury and plasma levels of DAO and LPS. Conclusions: This study of rats with SAP+IAH indicated that oral dosing of C. butyricum or butyrate reduced intestinal injury, possibly by altering the functions of the intestinal mucosal barrier.